2014
DOI: 10.24057/2071-9388-2014-7-4-68-79
|View full text |Cite
|
Sign up to set email alerts
|

New Permafrost Feature – Dep Crater in Central Yamal (West Siberia, Rusia) as a Response to Local Climate Fluctuations

Abstract: this paper is based on field data obtained during short visits to a newly formed permafrost feature in a form of relatively narrow, deep crater. excluding impossible and improbable versions of the crater's development, the authors conclude that it originated from warmer ground temperatures and an increase in unfrozen water content, leading to an increase in pressure from gas emissions from permafrost and ground ice. this conclusion is also supported by known processes in the palaeo-geography of yamal lakes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…Presumably, gas is continuously delivered from the gassaturated sediments under the lake and further oxidized in the water column. The extensive filling of the newly formed lakes with sediments from the retreating walls of GEC-1 and AntGEC 8,9 implies that initial gas flows can be restrained by a thick and relatively impermeable layer of silty-clayey and sandy sediments. Given average ground temperatures around the GEC-1 area of −1 to −5°C 28 we assume further freezing of sediments from below under the GEC-1 lake, probably forming a seal for further gas flows from beneath.…”
Section: Temperature Profilesmentioning
confidence: 99%
See 4 more Smart Citations
“…Presumably, gas is continuously delivered from the gassaturated sediments under the lake and further oxidized in the water column. The extensive filling of the newly formed lakes with sediments from the retreating walls of GEC-1 and AntGEC 8,9 implies that initial gas flows can be restrained by a thick and relatively impermeable layer of silty-clayey and sandy sediments. Given average ground temperatures around the GEC-1 area of −1 to −5°C 28 we assume further freezing of sediments from below under the GEC-1 lake, probably forming a seal for further gas flows from beneath.…”
Section: Temperature Profilesmentioning
confidence: 99%
“…For the first time in the terrestrial permafrost environment, gas emission craters (GECs) have been observed on the Yamal 7 and Gydan 8 peninsulas in summer and autumn 2014 ( Figure 1). The Yamal GEC (69.9711 N, 68.3703°E), 42 km from Bovanenkovo gas field, was named GEC-1 9 and the Gydan GEC near Antipayuta settlement (69.7946 N, 75.035°E) was named AntGEC. 8 Initially, these two permafrost-related features were deep and relatively narrow cylinder-shaped depressions with subvertical frozen walls and a funnel-shaped top.…”
mentioning
confidence: 99%
See 3 more Smart Citations